Numerical Study on the Shear Behaviour of Railway Ballast using Discrete Element Method - Venuja, S.; Navaratnarajah, S.K.; Jayawardhana, W.R.R.; Wijewardhana, P.H.L.; Nirmali, K.; Sandakelum, M.A.M. (Springer, 2023)
Rail transport is the most popular mode of transport where a large number of passengers and a large amount of freights are transported efﬁciently with econom- ical beneﬁts. Ballasted tracks are the widely used track foundation system around the world. Railway ballast is a coarse granular material with high bearing capacity and shear strength. The ballast layer uniformly transmits the loads from moving trains and sleepers to the underlying layers at a reduced level. When studying the behaviour of ballast under different loading conditions, a huge amount of ballast materials are consumed and it is very labour intensive work for large-scale laboratory tests. Nowadays, numerical studies are adopted by many researchers to reduce the usage of human resources and materials. And also, numerical studies enable extended anal- ysis through conducting a parametric study using the validated model. In this study, a numerical model was developed to study the shear behaviour of ballast and ballast– concrete interface using the discrete element method. Ballast with different shapes and sizes were modelled using multi-sphere clumps. The model was run under 30, 60, and 90 kPa normal stresses with a constant shearing rate of 4 mm/min as same as the laboratory test conditions. The model was validated using previous experimental results, and an acceptable agreement was observed for the ballast–concrete interface. The formation of the shear band in direct shear loading was observed by analysing the contact force distribution and the displacement vectors. The validated model can be used to study the change in shear behaviour of ballast when geogrid is inserted. Further, the model can be improved to incorporate the breakage of ballast particles.
Keywords: Discrete element method; Multi-sphere clump; Railway ballast; Shear band; Shear behaviour